Catherine de Médicis avant Catherine de Médicis - Pierre Nevejans (Medievalista)
Who was Catherine de’ Medici in Europe before she became Queen dowager? How did she think her place inside the princes’ society, considering she came from a branch that had been removed from power in Florence? This paper studies the Florentine diplomacy of the dauphine, from 1533 to 1547. It analyses as much its stakes as its tools and juridical foundations. It shows how heirs’ diplomacy, in this precise case study, roots within the margins of international law, onto domestic human resources, which gives the dauphine and her husband, future Henry II, the ability to forge their own political space, in the court of France, but also besides the kingdom’s limits. Founded on an important reconstruction of Catherine’s correspondence with her cousin, Cosimo I de’ Medici, duke of Florence (1537- 1574), this study travels through Early modern diplomacy’s meanders, within private archives, chancery registers and diplomatic correspondences, shedding light upon the flexibility that Isabella Lazzarini theorised.